Social relevance of the Quezon City Public Library System - Almoniña, John Ronald R.; Paragua, Jor-el E. (2013)
Public libraries are tasked to provide materials, programs, and services that cater to the needs of the community that it serves. It is the responsibility that serves to establish the public libraries as being socially significant and relevant. This study aimed to discover the extent of the Quezon city Public Library's significance to society based on its perceived effect in terms of these major social impact indicators: 1) Basic Literacy; 2) Business/Career; 3) The Library as a place; 4) Information Literacy; 5) General Information; 6) Empowerment; 7) Health and Well Being; 8) Personal Development; 9) Social Cohesion; and 10) Imagination/Creativity.